2019
DOI: 10.3390/ijms20061277
|View full text |Cite
|
Sign up to set email alerts
|

TM6SF2 and MBOAT7 Gene Variants in Liver Fibrosis and Cirrhosis

Abstract: Previous large-scale genetic studies identified single nucleotide polymorphisms (SNPs) of the TM6SF2 and MBOAT7 genes as risk factors for alcoholic liver cirrhosis and non-alcoholic fatty liver disease. In this study, we tried to evaluate the association between TM6SF2 variant rs58542926 and MBOAT7 variant rs641738 and the risk of hepatic fibrosis or liver cirrhosis of different etiology. In parallel, we also aimed to evaluate whether these two SNPs modify the effects of the PNPLA3 rs738409 risk variant for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
1
37
0
2
Order By: Relevance
“…Genome-wide association studies (GWAS) have identified the relationship between PNPLA3, TM6SF2, MBOAT7 single nucleotide polymorphisms (SNPs) and increased risk for chronic liver disease [12]. In previous studies, we found a significant association between PNPLA3 rs738409 and chronic liver injury in our cohort, although no significant associations between TM6SF2 and MBOAT7 variants were observed [13,14].…”
Section: Introductionmentioning
confidence: 42%
“…Genome-wide association studies (GWAS) have identified the relationship between PNPLA3, TM6SF2, MBOAT7 single nucleotide polymorphisms (SNPs) and increased risk for chronic liver disease [12]. In previous studies, we found a significant association between PNPLA3 rs738409 and chronic liver injury in our cohort, although no significant associations between TM6SF2 and MBOAT7 variants were observed [13,14].…”
Section: Introductionmentioning
confidence: 42%
“…2 5 NAFLD has also a strong genetic susceptibility, and among the genes of susceptibility 6 the single nucleotide polymorphism (rs641738 C>T) in the membrane bound O-acyltransferase domain-containing 7 (MBOAT7) gene increases the susceptibility to the entire spectrum of NAFLD, 7 8 by inducing a reduction in the liver MBOAT7 mRNA expression. [8][9][10][11] MBOAT7 encodes lysophosphatidylinositol acyltransferase 1 (LPIAT1), which preferentially incorporates arachidonic acid (AA; 20:4 n-6) into phosphatidylinositol (PI). [12][13][14] PI is a constitutive of membrane phospholipids and the precursor of signalling lipid phosphoinositides, 15 but so far no direct role of PI in TG synthesis has been shown.…”
Section: How Might It Impact On Clinical Practice In the Foreseeable mentioning
confidence: 99%
“…Genetic testing for risk alleles were in line with known distribution of disease severity 32 , 46 48 , but relative risk was too low to suggest a meaningful diagnostic benefit.…”
Section: Discussionmentioning
confidence: 99%